Estudo do pré-tratamento hidrotérmico e hidrólise enzimática da palha de cana-de-açúcar - Souza, Renata Beraldo Alencar de (2016)
The complex cell wall structure of lignocellulosic biomass makes pretreatment one of the most relevant 2G ethanol production process steps due to the difficulty of hydrolyzing lignocellulose to fermentable sugars and the cost of the process as a whole. The optimization of enzymatic hydrolysis conditions is crucial for reaching high yields that make the process feasible. In this way, the aim of this work is to assess the stages of pretreatment and enzymatic hydrolysis of the cellulosic fraction of straw sugarcane. All samples were chemically characterized before and after the pretreatment step. Hydrothermally pretreatment was evaluated in four conditions: 170ºC / 5 min, 170ºC / 15 min, 220°C / 5 min, 220°C / 5 min, and 195ºC / 10 min. Higher hemicellulose removal (85.58%) was found at 195ºC / 10 min. This operational condition was set as a reference. Hydrolysis experiments were carried out in Erlenmeyer flasks at 50ºC, 250 rpm and pH 4.8, with a reaction volume of 50 mL. Two sets of experiments were performed. In the first, the effect of substrate concentration was evaluated varying solid load (5; 10; 15; 20% msolid/vsolution) with enzyme load constant in 13 FPU.gbiomass. At 72h of enzymatic reaction, cellulose conversions were: 72% (5% of solids), 84% (10% of solids), 72% (15% of solids), and 59% (20% solids). In the second set, the enzyme (Cellic®CTec2) load effect (3; 7; 10; 13; 16; 40 FPU/gbiomass) with solid load settled at 15% (msolid/vsolution), was assessed. For assays with 15% of solid load, cellulose conversions were: 48% (3 FPU/gbiomass), 58% (7 FPU/gbiomass), 66% (10 FPU/gbiomass), 72% (13 FPU/gbiomass), 71% (16 FPU/gbiomass), and 74% (40 FPU/gbiomass). A trade-off between solid load and enzyme dosage was found (15% m/v and 13 FPU/gbiomass) which results in 72,4% of cellulose to glucose conversion. After that it was studied the products inhibition effect on hydrolysis was assessed. glucose and cellobiose (10 and 30g.L-1) caused a higher inhibitory effect. Xylose did not show the significant inhibitory effect on β-glucosidase. However, glucose and cellobiose had significant inhibitory effects on endoglucanase and exoglucanase as well as on β-glucosidase. Hydrolysis experiments were conducted in the batch reactor (3 L) with 10% solids to compare the performance with the hydrolysis conducted in Erlenmeyer flasks. At 72h hydrolysis cellulose to glucose, conversion was obtained in 84.8% (Erlenmeyer flask) and 80.2% (in the reactor); hydrolysis profiles obtained were similar in both conditions evaluated. In face of this, it was opted by conduct experiments in bioreactor (50 mL) using solid loads of 15 and 20% showed the best cellulose to glucose conversions when compared to those carried out in shake flasks in the same conditions.